The Development of Research Competencies, an Alternative to Train Childhood Educators as Teacher-Researchers - García-Gutiérrez, Zaily del Pilar (2019)
The training of professionals in charge of educating children is becoming increasingly important, given the impact this has on the quality of education and, likewise, on the improvement of a country’s social conditions. In this sense, this article presents the results about the development of research competencies in the training of professionals in child pedagogy, as a starting point to promote a qualification in this university program. Next, the theoretical perspective on training in research of the child pedagogy staff is developed. Then, the mixed-design methodology is explained; it was implemented through the survey, the focal group, and interviews applied to students, graduate students, teachers and directors, respectively. Once the information was triangulated, the results are presented; they express a favorable assessment of the processes. These processes were conducted by the program to enable the development of research skills, such as the capacity for analysis and reflection on the practice to contribute to children’s education, except for reading skills, on which there is a less positive assessment, and which constitutes a challenge for the university program to improve.